Microbial Quality of Sliced Pawpaw (Carica papaya) and Watermelon (Citrullus lanatus) Sold on Some Streets of Accra Metropolis, Ghana - Michael Olu-Taiwo; Baakwa Miah De-Graft; Akua Obeng Forson (International Journal of Microbiology)
In most African countries, street vending of fruits is prevalent and the likelihood of predisposing consumers to microbial contamination is very high. This study aimed to determine various bacteria and risk factors that are associated with fruits sold by street vendors in Accra. Sliced watermelons and pawpaws were randomly purchased from selected suburbs in Greater Accra Region of Ghana. One gram (1 g) of each watermelon and pawpaw was homogenized in 9 ml of sterile peptone water, and 0.1 ml from each serial dilutions of each fruit was spread on plate count agar, blood agar, and MacConkey agar plates for total aerobic counts and coliform counts. Agar plates were incubated at 33–37°C for 18–24 h. Bacterial identification was done by standard bacteriological methods. Additionally, questionnaires were administered to the vendors to gather data on food hygiene and knowledge on foodborne illness. The study revealed that although some of the fruit vendors were educated on food hygiene, most sold fruits were contaminated with mean total aerobic plate counts of 2.6 × 105–8.1 × 105 CFU g−1 and 3.7 × 104–7.1 × 104 CFU g−1 for watermelon and pawpaw. The mean coliform counts for pawpaw and watermelon ranged between 1.2 × 103–8.1 × 103 CFU g−1 and 1.6 × 104–3.1 × 104 CFU g−1, respectively. Overall, mean aerobic counts and mean coliform counts were not significantly different among vendors in selected locations p>0.05. However, predominant bacteria isolated included Enterobacter species (33.3%), Citrobacter sp. (20.0%), and Klebsiella sp. (15.9%). The study revealed that watermelon and pawpaw sold on the streets in Accra could be possible source of foodborne illness. Therefore, street food vendors must be educated on food hygiene protocols and measures to improve microbial quality of street vended fruits.